Evaluasi Pembelajaran Terhadap Sikap Peserta Didik di Sekolah Dasar - Hildasari Amanda; Dova Kridhayana; Wildah Akbar Andika (Universitas PGRI Madiun, 2026)
Evaluation of learning attitides is an importanr component in elementary education because education is not only oriented toward cognitive achievement but alsi toward the formation of students’ character. This article aims to analyze the concept , principles, techniques, and implementation of attitude evaluation in elementary school. The method used in this study is a literature review by analyzing varios books, educational guidelines, and relevant research article related to learning evaluatin and character education. The result of study show that attitude evaluarin in elementary school plays an important role in identifiying students;s spiritual and social development. Attitude assessment can be carried out thriugh observation, self-assessment, peer assessment, dan teacher journal. Effectve attitude evaluation requires objective, continuoes, comprehensive, transparent, and ecucational principles. However, teacher still face challenges such as limited time, large numbers of student, and difficulties in determinining objective indicators. Therfore, teachers need appropiate strategies and instrument to conduct attitude evaluation as part of sterngthening student character.